Pengaruh Digital Marketing Dan Harga Jual Terhadap Omzet Penjualan UMKM: Studi Pada Pedagang Pusat Grosir Metro Tanah Abang Blok B - Kezia Angelita; Budi Santosa Kramadibrata (Universitas Kristen Indonesia Toraja, 2024)
Tanah Abang Metro Wholesale Center traders have experienced a thematic economic decline since the rise of online business presence. Digital marketing as a two-way communication method that can increase public engagement with certain products and brands. Digital marketing is slowly being adopted by MSMEs, although conventional marketing is still mostly relied on by many MSMEs, especially micro circles. This study aims to determine the influence of digital marketing and selling prices on sales turnover at the Tanah Abang Metro Wholesale Center Block B on 149 respondents who have done digital marketing. The instrument used in this study is a questionnaire, with instrument testing including validity test and reliability test. Data analysis used descriptive analysis, hypothesis testing using multiple linear regression analysis along with t-test, f-test and R2 test. The results of the study show that (1) digital marketing has an effect on sales turnover, (2) selling price has an effect on sales turnover, (3) digital marketing and selling price simultaneously affect sales turnover.